Case Report: Chronic Active Epstein–Barr Virus Infection With Subcutaneous Nodules and Systemic Damage - Luo, Huating; Yuan, Zhe; Qin, Bo (Frontiers in Medicine, 2022)
Chronic active Epstein-Barr virus (CAEBV) infection is a rare and progressive systemic lymphoproliferative disorder often beginning as an infectious mononucleosis (IM)-like illness. It manifests with fever, splenomegaly, hepatitis, lymphadenopathy, and occasionally cytopenias, pneumonitis, and vasculitis. The incidence of CAEBV cutaneous lesions is low and rarely reported. Typical skin manifestations include mosquito bite allergy and hydroavacciniforme (HV)-like skin changes. We report a 23-year-old female with fever and subcutaneous nodules first appearing on the limbs and then spreading to the body. Peripheral blood EBV antibodies were elevated and EBV-DNA loads significantly increased. A skin and lymph node biopsy identified T-cell-based lymphocyte infiltration and EBV-encoded RNA positivity (EBER+). CAEBV was finally diagnosed. During the illness, her disease progressed to hemophagocytic syndrome (HPS). The patient then successfully received an allogeneic hematopoietic stem cell transplantation (HSCT) at six months. Current follow-up at 2 years indicated a stable condition and six negative EBV-DNA tests, we reviewed the clinical manifestations，mechanism, diagnosis and differential diagnosis, treatment and prognosis of CAEBV. Finally, subcutaneous nodules may occur when CAEBV invades the skin, therefore clinicians must identify the cause of these nodules early. HSCT is effective but its timing must be appropriate.